Root canal treatment of three-rooted maxillary first and second premolars - a case report - Soares, J. A.; Leonardo, R. T. (Blackwell Publishing, 2003)
Aim To report the diagnosis and successful clinical management of a patient with anatomical variation in maxillary first and second premolars.Summary Maxillary premolars have a highly variable root canal morphology, but it is rare, especially in the second premolar, to find three canals. This article describes the diagnosis and clinical management of first and second premolars with three canals and three separate roots, drawing particular attention to radiographic interpretation and access refinements.
Keywords: anatomical variations; maxillary premolars; root anatomy